Economic Models used by Shipping Decision Makers: Array - (Marcu) Turcanu, Andra Luciana; Gasparotti, Carmen; Raileanu, Alina Beatrice (EuroEconomica, 2021)
Transport economics is the branch of economic science whose object and purpose are to interpret and substantiate theoretically "and practically" the facts, acts, and economic behaviors that meet the needs of movement, distribution, and physical distribution of resources of goods, products, goods, and people, by use of transport capacities. The purpose of this paper is to present different approaches of modeling and simulation economic processes. It is known that those methods managers can apply a wide range of management methods and techniques. From the practice of economically developed countries, the manager uses modeling as an alternative to the exact sciences. Computer-assisted modeling is based on the idea that man cannot be excluded from running a system. He is the primary source of formulating hypotheses about system behavior and the only one to include the results of different evolutionary variants in an integrative action.